-2x - 2√x(1+x)
1 + 2x + 2√x(1+x)
√x(1+x)
1 + 2x - 2√x(1+x)
Correct answer is B
√1+x+√x√1+x−√x
= (√1+x+√x√1+x−√x)(√1+x+√x√1+x+√x)
= (1+x)+√x(1+x)+√x(1+x)+x(1+x)−x
= 1+2x+2√x(1+x)1
= 1+2x+2√x(1+x)
In the diagram, TS is a tangent to the circle at S. |PR| and < PQR = 177o. Calculate < PST....
If (-3, -4) is a point on the line y = mx + 2 find the value of m....
If the mean of the numbers 0, (x+2), (3x+6), and (4x+8) is 4, find their mean deviation. ...
Simplify (2m−u)2−(m−2u)25m2−5u2...
Which inequality describes the graph above? ...
At what rate would a sum of N100.00 deposited for 5 years raise an interest of N7.50?...